Who are you, who am I? : The potentials of aDNA research in inhumation burials of Pre-Roman Iron Age Finland - Niemelä, Aster (My University, 2024)
A literature review on the Baltic-Finnic ethnogenesis, the Pre-Roman Iron Age in Finland as well as aDNA research shows potential for not only future aDNA research on the Pre-Roman Iron Age, but other research methods as well. Other fields such as linguistics should also not be ignored, especially when it comes to researching ethnogenesis. The literature review fo-cused on literature, both archaeological and biological, that centered on cemeteries. Due to the acidity of Finnish soil research on organic samples has been deemed difficult – but as the study shows, not impossible. Newer and more efficient methods are constantly discovered, and the future of aDNA research on the Pre-Roman Iron Age in Finland has potential. This thesis concludes that as of right now, aDNA results from the Pre-Roman Iron Age have been slim but using other methods alongside extracting aDNA raises the potential and can provide more thorough results on the inhabitants of Pre-Roman Iron Age Finland. Future methods and research can tell us more about migration events and when the genetic admixture of Finns was formed.
Keywords: aDNA, ethnogenesis, Finland, haplogroups, literature review, methods of natural sciences, Pre-Roman Iron Age, tarand cemeteries